Preventing Drug Demand in Criminal Policy: A Comparison of Educational Strategies in Britain, Iran and the United States - Zahra Ahngari Nanekaran; Seyed Mahmood Mirkhalili; Seyed Hasan Hashemi; Mehdi Sheydaeian (Comparative Education Society of Iran ( CESIR), 2021)
The purpose of this study is to compare the educational Strategies of Britain, Iran, and the United States to prevent drug demand among the young generation. In this comparative study, the researchers used a documentary method to collect data, and a "thematic content analysis" approach for data analysis. The first finding of the study points to the similarity of the three countries in the upward trend in drug use among the younger generation. The second finding is that the criminal policy of Britain and the United States in the fight against drug use is mainly demand-oriented, while the supply-oriented approach is still prevalent in Iran. Another finding reveals the similarity of the criminal policies of the three countries in the field of intolerance of the distribution of any drugs among students. The research findings also indicated that in Iran the variety of drugs (especially psychedelics) is higher but the percentage of students consuming is lower, while in Britain and the United States the percentage of young consumers is higher but the variety of drugs is less. In addition, the research showed that the variety and scope of educational programs and schemes, as well as the active presence of non-governmental organizations in schools to combat drug use in Britain and the United States is greater than in Iran. Considering the findings, it is suggested to the Iran's legal and educational legislators to make reforms such as emphasizing the demand-based approach, adoption of laws related to promoting the participation of non-governmental organizations, and increasing the coverage of educational strategies to combat drug use